A proposal of an evaluation method for hydraulic standard force machine. (December 2021) - Maldonado, Nestor Isaac; Betancur, Iván David
Abstract: This paper describes a new method to evaluate the behavior of the 1000 kN hydraulic amplification force standard machine that belongs to the National Metrology Institute from Colombia (INM). The proposed method is based on taking measurements in 4 force transducers of different capability and load direction. These measurements are taken both in a deadweight force standard machine (DFM) and in the reference hydraulic machine (RHM). The average values of the increasing measurements obtained in each type of machine are compared. As a result, the behavior of the RHM is determined and an estimate of its drift is proposed.